Application of Appropriate Technology To Overcome Problems weather in SMEs Madiredo district. Pujon Kab . Malang - Sigit Kusmaryanto (Journal of Innovation and Applied Technology, 2015)
ABSTRACTOnion crackers effort Madiredo Pujon Malang district originally had one group of workers housewife mother were four people , which then evolved into two groups scattered in two regions Madiredo RW in the village district. Malang Regency. These efforts have started to grow and become a pilot effort in the village Madiredo Pujon Malang. Enterprises managed onion crackers mothers still constrained on the weather conditions. Crackers drying process is done by drying the sun in an open area.  A decline in capacity and quality if the weather is cloudy or rainy. In relation to the problems faced by business group of crackers onion SMEs Village Madiredo Pujon Malang regency are , in the activities of Community Service is an attempt application of appropriate technology that is drier chips that aim to guarantee the sustainability of the production process without being disturbed by the weather conditions and the limited area drying.The results obtained from the activities of Community Services are shorter than the drying process by drying the manual / regular . With the drier the drying time for 4 hours of drying , while no dryers require a drying time 7 hours ( dry season ) and 4 days during the rainy season . Namely an increase in production capacity mean the dryer is capable of producing 50 kg / day / SME .Keywords : Tools dryer , onion cracker, SMEs